Pre–Post Tornado Effects on Aggressive Children's Psychological and Behavioral Adjustment Through One-Year Postdisaster. Issue 1 (2nd January 2017) - Lochman, John E.; Vernberg, Eric; Powell, Nicole P.; Boxmeyer, Caroline L.; Jarrett, Matthew; McDonald, Kristina; Qu, Lixin; Hendrickson, Michelle; Kassing, Francesca
Abstract : Using a risk-resilience framework, this study examined how varying levels of exposure to a natural disaster (EF-4 tornado) and children's characteristics (sex; anxiety) influenced the behavioral and psychological adjustment of children who shared a common risk factor predisaster (elevated aggression) prior to exposure through 1-year postdisaster. Participants included 360 children in Grades 4–6 (65% male; 78% African American) and their parents from predominantly low-income households who were already participating in a longitudinal study of indicated prevention effects for externalizing outcomes when the tornado occurred in 2011. Fourth-grade children who were screened for overt aggressive behavior were recruited in 3 annual cohorts (120 per year, beginning in 2009). Parent-rated aggression and internalizing problems were assessed prior to the tornado (Wave 1), within a half-year after the tornado (Wave 2), and at a 1-year follow-up (Wave 3). Children and parents rated their exposure to aspects of tornado-related traumatic experiences at Wave 3. Children displayed less reduction on aggression and internalizing problems if the children had experienced distress after the tornado or fears for their life, in combination with their pre-tornado level of anxiety. Higher levels of children's and parents' exposure to the tornado interacted with children's lower baseline child anxiety to predict less reduction in aggression and internalizing problems 1 year after the tornado. Higher levels of disaster exposure negatively affected at-risk children's level of improvement in aggression and internalizing problems, when life threat (parent- and child-reported) and child-reported distress after the tornado were moderated by baseline anxiety.